PERAN ORANG TUA DALAM MEMBANGUN POTENSI ANAK - Dr. Mukhlis Mukhtar (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2018)
Man is positioned by Allah swt as the most perfect and honorable being. To preserve the existence of man, then God grant to the human hearing, sight and heart. Then the mother of his father was given the trust of Allah swt. to develop the sensitivity of hearing, sight and feeling (the heart) as a foundation in building two capabilities, namely the actual ability and potential ability. Actual ability is the ability that has been actualized or the ability that has real manifestation, while potential ability is a capability that has not been explored, not actualized or the ability tangible possibilities. To develop the potential ability, then the parents are obliged as follows: 1. Memidizing the creed of his son, because Allah swt. has put the value of faith on every child (human) since still in the womb of his mother. 2. Knowing and understanding the child's character, learning style, learning motivation. 3. Seek the creation of an educational environment that can foster all aspects of development that includes mental, interest, creativity in a balanced and optimal. 4. Developing children's potential through creativity